2018
DOI: 10.1055/s-0038-1676523
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between Patellofemoral Alignment and Osgood–Schlatter Disease? A Case-Control Study

Abstract: This study was aimed to investigate the role of anatomic variations in patellofemoral alignment in patients with or without Osgood-Schlatter disease (OSD) and to determine the potential anatomic risk factors that may play role in the etiology. This prospective observational case-control study was conducted on two groups of adolescent patients. Group 1 comprised patients who were diagnosed as having OSD and group 2 consisted of an equal number of age-matched patients who presented to the outpatient clinic with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Of the 40 studies included, 25 studies reported on OSD‐related imaging findings 4‐7,9,11‐30 . Most studies used radiography (n = 10) or US (n = 6), with the remaining studies using radiography and US (n = 4), radiography and MRI (n = 3), MRI only (n = 1) and one study using both CT, MRI, radiography, and bone scintigraphy (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 40 studies included, 25 studies reported on OSD‐related imaging findings 4‐7,9,11‐30 . Most studies used radiography (n = 10) or US (n = 6), with the remaining studies using radiography and US (n = 4), radiography and MRI (n = 3), MRI only (n = 1) and one study using both CT, MRI, radiography, and bone scintigraphy (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eight cross‐sectional 4,15,20,24,27‐30 and two case‐control studies 6,7 reported on OSD imaging findings compared to controls. In the studies that included a control group, the imaging findings described above (Table 1) were not observed in the controls without OSD 4,7,15,27 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At six months postoperatively, radiological assessment was performed by two independent observers, who did not know the patient's clinical information. Insall-Salvati index [ 22 ], Blackburne-Peel index [ 23 ], congruence angle [ 24 ], and lateral patellofemoral angles [ 25 ] were measured using lateral and Laurin knee radiograph. The measurement was repeated three times, and the average of the measurements was used for the final analysis.…”
Section: Methodsmentioning
confidence: 99%